Prevalence of Scabies and Associated Factors in the Rural Area of Maraka, Punjab, Pakistan (Journal of Fatima Jinnah Medical University, 2026)
Background: Scabies has a high global burden affecting more than 200 million people worldwide. Scabies has been a major burden on dermatological presentations in Pakistan. This study aimed to determine the prevalence of scabies and identify associated factors among residents of a rural area of Maraka, Punjab, Pakistan.Methods: A cross-sectional study was conducted in Maraka village, Punjab, with a sample of 250 participants from May to September 2023. The data were collected using systematic random sampling. A structured questionnaire was formulated to collect data.Results: A high rate of prevalence of scabies was found, as 50.4% of the sample population had signs of clinical scabies. Risk factors for contracting scabies included unemployment status (43.7%, p-value =0.006), family income of less than 30,000 PKR (74.7%, p-value = 0.050), joint family system (53.4%, p-value = 0.005), and living in close quarters (64.1%, p-value = 0.001). Significant association of developing clinical scabies was observed with positive travel history to endemic areas (39.8%, p-value = 0.001), history of scabies in partners (54.4%, p-value = 0.001), frequent skin-to-skin contact (58.3%, p-value = 0.001), and history of itching in sexual partners (24.3%, p-value = 0.001). The most common presentation was nighttime itching (41.2%, p-value = 0.001). The most common affected area was the armpits (26.2%), followed by the finger webs (25.2%; p-value = 0.001). A family history of scabies was strongly associated with clinical scabies (54.4%, p-value = 0.001).Conclusion: Scabies was reported to be high in the participants in Maraka. Lower socio-economic groups and those living in proximity are more likely to contract scabies. Family history and particularly scabies in partners pose a major risk factor for developing scabies.
Keywords: Scabies; Prevalence; Risk Factors; Rural Population; Socioeconomic Status; Pakistan